Head-to-tail interactions of the coiled-coil domains regulate ClpB activity and cooperation with Hsp70 in protein disaggregation - Carroni, Marta; Kummer, Eva; Oguchi, Yuki; Wendler, Petra; Clare, Daniel K; Sinning, Irmgard; Kopp, Jürgen; Mogk, Axel; Bukau, Bernd; Saibil, Helen R (eLife, 2014)
The hexameric AAA+ chaperone ClpB reactivates aggregated proteins in cooperation with the Hsp70 system. Essential for disaggregation, the ClpB middle domain (MD) is a coiled-coil propeller that binds Hsp70. Although the ClpB subunit structure is known, positioning of the MD in the hexamer and its mechanism of action are unclear. We obtained electron microscopy (EM) structures of the BAP variant of ClpB that binds the protease ClpP, clearly revealing MD density on the surface of the ClpB ring. Mutant analysis and asymmetric reconstructions show that MDs adopt diverse positions in a single ClpB hexamer. Adjacent, horizontally oriented MDs form head-to-tail contacts and repress ClpB activity by preventing Hsp70 interaction. Tilting of the MD breaks this contact, allowing Hsp70 binding, and releasing the contact in adjacent subunits. Our data suggest a wavelike activation of ClpB subunits around the ring., DOI: - http://dx.doi.org/10.7554/eLife.02481.001, Proteins are long chain-like molecules that twist and fold into complex three-dimensional shapes in order to carry out their functions. High temperatures or other types of stress can cause proteins to fold incorrectly, and misfolded proteins can form clumps (or aggregates) that are harmful to cells. Additional proteins called chaperones are therefore used by cells to help proteins to fold correctly, or to refold poorly folded proteins., ClpB proteins (and related proteins) are chaperones found in bacteria, fungi and plants; these proteins co-operate with other chaperones to rescue misfolded proteins that have aggregated—an activity that helps cells to survive heat shock and other stresses. Six ClpB proteins work together to form a ring-shaped complex, and the misfolded protein is unfolded by threading it through the centre of this ring. Each ClpB protein also has a middle domain that acts to switch the complex on and off as needed., The middle domains are known to form coiled-coils, with protein helices coiled together like the strands of a rope. However, previous efforts to work out the structure of the ClpB complex did not clearly establish where these coiled-coils were positioned relative to the rest of the ring., Now Carroni et al. have used image processing to overcome these problems and reveal that the middle domains are wrapped around the outer edge of the ring complex. Analysis of ClpB mutants that lock the complex in either an off or on state revealed that the middle domains are linked head-to tail to encircle the ring when the complex is off. However, when the complex switches on, the middle domains let go of each other and tilt, allowing the ring to change shape. Carroni et al. suggest that the exposed ends of the middle domains are free to bind to other chaperones (those that work to refold the unfolded proteins), thereby activating the complex., Although Carroni et al. have revealed how the ClpB ring complex is activated, further work is needed to understand exactly how the unlocked ring works to rescue misfolded proteins from aggregates within cells., DOI: - http://dx.doi.org/10.7554/eLife.02481.002